Pendekatan Play Therapy pada Konseling Krisis - Mardes, Siska; Ratnadillah, Winda; Rahma Dhani, Aulia; Yani, Helma; Hayati, Ainul; Yulia Pratiwi, Dwi; Azzahra, Khalisa (diterbitkan oleh Program Studi Bimbingan dan Konseling FKIP Universitas Sriwijaya Jl. Palembang Prabumulih KM 3.2 Palembang-Indonesia Email: jkk@fkip.unsri.ac.id, 2025)
Crisis is a situation filled with tension that can affect an individual's physical, emotional, and psychological condition. One of the world's biggest mental health challenges is depression, which affects many individuals. In the context of a crisis, crisis counseling plays a crucial role in providing psychological support and helping individuals manage feelings of panic and uncertainty. This study aims to examine the application of play therapy in crisis counseling. The method used is a literature review, analyzing various sources of literature discussing the implementation of play therapy in crisis counseling. The results of the analysis show that play therapy, through its procedures of therapy planning, implementation, and evaluation, can be an effective approach in psychological intervention for children experiencing trauma due to crises. Routine evaluation is recommended to ensure the effectiveness of the therapy, and further research is needed to explore its application in various types of crises faced by children.